‘Let Me Also Say What I Think!’ On Wincenty Ignacy Marewicz’s Political Poetry and Active Patriotism - Balaišytė, Lina (Senoji Lietuvos literatūra, 2024)
The article focuses on Wincenty Ignacy Marewicz’s (1755–1822) political poetry. The man of letters, who lived in Vilnius in the late eighteenth century, was an active participant in the processes unfolding in the state, an ardent critic of society, and a supporter of reforms. His political poetry responded to the political events of the time and should be seen not in an artistic sense but rather as a political statement. The article examines Marewicz’s work through a social and political prism: it is regarded as an original source showing an individual’s relation to current political events and capturing the communal values of the epoch. Marewicz’s political writing was shaped by the highly politicised environment of Warsaw during the period of the Four-Year Sejm, but much of it was written in Vilnius, where the writer became involved in public activities. In his works, Marewicz supported the activity of the ruler and the Patriotic Party, welcomed the Constitution of 3 May 1791, supported the extension of the rights of the townspeople, and called for a struggle against the enemies of the homeland. The motifs of Marewicz’s works were characteristic of patriotic poetry of the late eighteenth century: he wrote about the realities of a specific time (resolutions of the Four-Year Sejm, the actions of foreign powers, and the like), and used revolutionary topics. As often preached by the literati from the poor nobility and the urban population, he, too, explored the ideas of egalitarianism and social solidarity. However, Marewicz’s response to political events in the country was deeply personal. Although he considered himself a little man, he, as a citizen and a nobleman, felt entitled to expose the ills of society and to advise the powerful on how to rectify them. He viewed people’s actions from the perspective of the public interest, and was an advocate of activism for the good of the homeland himself. In his works, he also reflected on the reasons of the collapse of the state: he discerned not only the fault of hostile foreign powers and local traitors, but also the flaws in the society of the Republic: the lack of unity and placing self- interests above all else. From the temporal perspective (in Nefelonikones, 1821), the poet offered a different view of the events of the late eighteenth century: he blamed the collapse of the state on the egoism of the king and the nobility, their unwillingness to liberate the peasantry and to express solidarity with all the estates.